Molecular Epidemiology of Cryptosporidiosis in China - Feng, Yaoyu; Xiao, Lihua (Frontiers in Microbiology, 2017)
Molecular epidemiology of cryptosporidiosis is an active research area in China. The use of genotyping and subtyping tools in prevalence studies has led to the identification of unique characteristics of Cryptosporidium infections in humans and animals. Human cryptosporidiosis in China is exemplified by the high diversity of Cryptosporidium spp. at species and subtype levels, with dominant C. hominis and C. parvum subtypes being rarely detected in other countries. Similarly, preweaned dairy calves, lambs, and goat kids are mostly infected with non-pathogenic Cryptosporidium species (C. bovis in calves and C. xiaoi in lambs and goat kids), with C. parvum starting to appear in dairy calves as a consequence of concentrated animal feeding operations. The latter Cryptosporidium species is dominated by IId subtypes, with IIa subtypes largely absent from the country. Unlike elsewhere, rodents in China appear to be commonly infected with C. parvum IId subtypes, with identical subtypes being found in these animals, calves, other livestock, and humans. In addition to cattle, pigs and chickens appear to be significant contributors to Cryptosporidium contamination in drinking water sources, as reflected by the frequent detection of C. suis, C. baileyi and C. meleagridis in water samples. Chinese scientists have also made significant contributions to the development of new molecular epidemiological tools for Cryptosporidium spp. and improvements in our understanding of the mechanism involved in the emergence of hyper-transmissible and virulent C. hominis and C. parvum subtypes. Despite this progress, coordinated research efforts should be made to address changes in Cryptosporidium transmission because of rapid economic development in China and to prevent the introduction and spread of virulent and zoonotic Cryptosporidium species and subtypes in farm animals.